2015
DOI: 10.1108/jrim-02-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of brand communication on brand equity through Facebook

Abstract: The impact of brand communication on brand equity through FacebookPurpose: The purpose of this study is to fill the gap in the discussion of the ways in which firm-created and user-generated social media brand communication impacts consumer-based brand equity metrics through Facebook.Design/methodology/approach: We evaluated 302 data sets that were generated through a standardized online-survey to investigate the impact of firm-created and user-generated social media brand communication on brand awareness/asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
252
1
34

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(311 citation statements)
references
References 70 publications
24
252
1
34
Order By: Relevance
“…As past research has found that the development of team loyalty and attaching meanings to an environment can foster socialization in the stadium (James, 2001;Lee et al, 2013;Melnick, 1993). Moreover, the conclusion from Petrick's (2004) study that loyal tourists are more likely to revisit and spread (Schivinski and Dabrowski, 2015). The fact that the environmental framework exhibits explanatory power indicates the need for the investigation of other relevant behavioral constructs in the context of spectator sport.…”
Section: Discussionmentioning
confidence: 98%
“…As past research has found that the development of team loyalty and attaching meanings to an environment can foster socialization in the stadium (James, 2001;Lee et al, 2013;Melnick, 1993). Moreover, the conclusion from Petrick's (2004) study that loyal tourists are more likely to revisit and spread (Schivinski and Dabrowski, 2015). The fact that the environmental framework exhibits explanatory power indicates the need for the investigation of other relevant behavioral constructs in the context of spectator sport.…”
Section: Discussionmentioning
confidence: 98%
“…Purchase intention was measured using three items adapted from the research of Yoo, Donthu, and Lee (2000) and Shukla (2011). Finally, firm-created and usergenerated social media communication were measured using four items adopted from Mägi (2003), Tsiros, Mittal, and Ross (2004), and Schivinski and Dabrowski (2013). The complete list of items can be found in Table I of Appendix A.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, as a result of the huge value of social media advertising and youth spending power, further research is warranted. Much research has been dedicated to social media advertising on digital platforms such as Facebook, Twitter and YouTube (Smith et al, 2012;Hudson and Hudson, 2013;Logan, 2014;Kananukul et al, 2015;Leung et al, 2015;Schivinski and Dabrowski, 2015), but there is a dearth of research on IM advertising. WhatsApp is the second most popular social media channel in SA, and is also one of the largest global IM platforms.…”
Section: Introductionmentioning
confidence: 99%